INTERAKSI SIMBOLIK DALAM PROSES KOMUNIKASI NONVERBAL PADA APLIKASI TIKTOK - Eka Putri, Ni Luh Wiwik (Widya Duta: Jurnal Ilmiah Ilmu Agama dan Ilmu Sosial Budaya, 2019)
The emergence of communication technology, such as Smartphones has changed the pattern of individual communication in society. They can communicate without having to face to face directly with each other. Smartphones pamper their users with features and applications that are constantly updated due to human needs and requests. One application that is now widely enjoyed by the public is the TikTok application. Designed for the new generation of content creators, TikTok allows users to create short, unique videos that are fast and easy to use various special effects to share with friends and the world. Whether in the form of dance, comedy, free-style or other performance acts. Through the TikTok application can also make people become famous, some of them are @bowoo_alpenliebe, @Nurraini, @Nadia Zerlinda. In symbolic interaction through Lipsync as a means of communication in Tiktok Bowo interpreted his resentment towards the ex, because with his prank, he teased Iqball, then Zerlinda expressed his feelings towards someone he loved. While symbolic interaction through body language and tiktoker gestures, among others, is shown through gesture seen from nonverbal activities in three ways, namely: 1) the original source of actions such as facial expressions; 2) marking or coding such as body movements and their meaning 3) the use of communicative actions to convey meaning and interactive actions to influence the behavior of participants or other parties.